(untitled) (Research, Society and Development, 2026)
Sweet pepper (Capsicum annuum L.) is a vegetable crop of high economic relevance in Brazil and shows good adaptation to different growing conditions, including semiarid regions such as Irecê, Bahia. This study aimed to evaluate the application of two foliar fertilizers at different rates on the performance and quality of sweet pepper seedlings under protected cultivation. The experiment was carried out in a greenhouse using a randomized complete block design, with five treatments and six replications. Morphological and biomass traits were measured, including number of leaves, stem diameter, root and shoot length, plant height, fresh mass (root, shoot, and total), and total dry mass. Analysis of variance indicated no significant differences among treatments for the evaluated variables. Therefore, under the conditions of this study, foliar fertilizer application at the nursery stage showed no agronomic relevance for improving seedling quality, suggesting that its use may be unnecessary at this stage. These results highlight the need for technical validation before recommending foliar fertilization for early sweet pepper development, considering environment, management practices, and the formulations used.